2011
DOI: 10.1007/s00580-011-1304-6
|View full text |Cite
|
Sign up to set email alerts
|

Presumptive histiocytic neoplasm with unusual immunophenotype in a cat

Abstract: True histiocytic proliferative diseases have been infrequently documented in the cat, with progressive histiocytosis and histiocytic sarcoma representing the bulk of the reported cases. A 5-year-old, neutered male domestic shorthair cat presented with a 1-month history of anorexia, depression, mucosal pallor and persistent non regenerative anemia. On admission, the cat appeared depressed, icteric, dyspneic and had moderate splenomegaly. The cat had a severe, temporarily regenerative anemia, and a blood smear e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Phagocytosis of blood cells and their precursors is rare in the BM of healthy animals and generally involves only mature erythrocytes (Harvey, 2012b). Frequent BM erythrophagocytoses may occur in immune-mediated hemolytic anemias, in erythrocytic parasites (e.g., Babesia sp., hemoplasmosis), hematopoietic neoplasms, after blood transfusion, and in histiocytic neoplasia, including the hemophagocytic histiocytosis (Mylonakis et al, 2012), while idiopathic cases have also been reported (Weiss, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Phagocytosis of blood cells and their precursors is rare in the BM of healthy animals and generally involves only mature erythrocytes (Harvey, 2012b). Frequent BM erythrophagocytoses may occur in immune-mediated hemolytic anemias, in erythrocytic parasites (e.g., Babesia sp., hemoplasmosis), hematopoietic neoplasms, after blood transfusion, and in histiocytic neoplasia, including the hemophagocytic histiocytosis (Mylonakis et al, 2012), while idiopathic cases have also been reported (Weiss, 2007).…”
mentioning
confidence: 99%
“…These features were also demonstrated in spleen aspirates (not shown) (Giemsa, x400). [From:Mylonakis ME et al, (2012) Presumptive histiocytic neoplasm with unusual immunophenotype in a cat. Comp Clin Pathol, 21: 231-236].…”
mentioning
confidence: 99%